2016
DOI: 10.12669/pjms.323.9978
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study assessing the outcome of Sepsis in intensive care unit of a tertiary care hospital, Peshawar

Abstract: Objective:The current study aims to explore the factors associated with outcome among patients with severe sepsis and septic shock admitted to the intensive care unit, Northwest General Hospital and Research Centre, Peshawar, Pakistan.Methods:A prospective observational study was carried out at intensive care unit of our hospital from February 2014 to October 2015. Data was collected using a structured format and statistical analysis was done using SPSS version 20®. Regression model was applied to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Our study evaluated and compared performance of the qSOFA score and SOFA in septic ED patients from a low to middle income country with a high reported severity of illness and mortality than quoted locally 3 , 22 as well as those from high income nations. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Our study evaluated and compared performance of the qSOFA score and SOFA in septic ED patients from a low to middle income country with a high reported severity of illness and mortality than quoted locally 3 , 22 as well as those from high income nations. 17 …”
Section: Discussionmentioning
confidence: 99%
“…occurs in approximately 2% of all hospitalised cases and among 6-30% of all patients admitted to intensive care units (ICUs) in developed countries. 3,4 Both sepsis and septic shock are leading causes of morbidity and mortality in ICUs (21% and 28%, respectively). [4][5][6] The management of sepsis or septic shock requires a comprehensive and systematic approach combining the use of appropriate diagnostic measures, the rapid initiation of appropriate empirical antibiotics and the administration of supportive therapy.…”
mentioning
confidence: 99%
“…For example, although mortality rates of 6-11% have been recorded following abdominal infection, 19,20 after the infection has progressed to septic shock, the risk of death increases dramatically. 21 One study found that the 7-day mortality of patients with pyelonephritis and septic shock was 26% while those without septic shock was zero. 22 Our study showed that high SOFA scores on Day 1 were associated with increased risk of death.…”
Section: Discussionmentioning
confidence: 99%